(untitled) (Revista de Ciências Agroveterinárias, 2023)
This study aimed to assess the effectiveness of two clarifying procedures and their effects on some properties in thermally or microwave-pasteurized pomegranate juices. The experiment consisted in combining pectinase and protease as well as chitosan and gelatin once they were being stored in the refrigerator. The experiment consisted in three parts, being the first one a fresh juice without any clarification treatment, whereas, the second one was the fresh juice treated with clarifying agent consisted of pectinase and protease mixture ratio (2:1) at 0.75 v/v,and 50 °C for 20 min. Finally, the third one was fresh juice treated with chitosan and gelatin mixture at 0.4 and 0.8) g/L, respectively, at 50 °C for (20) min. The pasteurization of all three experiments was done by using two techniques, i.e., one with thermal water bath at 85 °C for two min and the microwave at 400 Watts for two min. All pomegranate juice bottles were stored at 4 °C for three months. The results showed a significant effect of the clarification method variable on the properties studied, especially turbidity, polyphenol and anthocyanin values. Moreover, the juice clarified with the enzymatic clarification method had better characteristics than the traditional ones during storage, what has therefore a better commercial appeal. The area of significance was founded with the use of traditional clarification with concentration at (0.4 and 0.8) g/l, and microwave pasteurization with 400 watts and zero month of storage at 4 °C, respectively, which is provided a minimum turbidity value.